Assessment of Quality of Life for Parents of Autistic Child - dawood, Kawther; Khudhair, ali (Iraqi National Journal of Nursing Specialties, 2016)
Objectives: The study aims to assess the QOL for parents of a child with autism Methodology: A descriptive study was conducted on parents of autistic child in Baghdad city. A purposive (non-probability) sample of (156) parents, (78) mothers and (78) fathers of (78) autistic children who are clients and receive care in the private specialization centers for autism were selected to participated in the current study. The study used a self- administrative questionnaire for data collection. Results: The findings indicated that both parents (mothers and fathers) were participated in this study, and they comprised an equal number (78). Both parents reported a moderate level of QOL. Mothers were reported a lowest levels of psychological well-being, physical well-being and environmental comfort than fathers. There is a significant difference between mothers and fathers in psychological and physical domains of QOL level. Recommendations: Parents with autistic child especially mothers need more attention and support in all aspects of their lives that have been correlated with their QOL. Keywords: Quality of Life, Parents, Child, Autism.